Towards an effective appraisal model in the evaluation of teacher quality in two districts, Limpopo Province - Bokgola, Mogalapitja Sybil (University of Limpopo, 2015)
The purpose of the study was to explain how teacher evaluation is implemented in sampled schools of two districts; Mogalakwena and Waterberg of the Limpopo Province. The interpretive paradigm was followed to investigate how teachers at the sampled schools implement teacher evaluation, Integrated Quality Management System (IQMS). Within the interpretive paradigm, qualitative approach was followed to gain an in-depth understanding of social realities as well as comprehensive portrait of range of attempts, interactions, situations and perceptions. Data collection was done using interviews, observations and document analysis. Twenty-four participants participated in the study (eight principals; eight School Developmental Teams (SDTs) and eight teachers). Principals provided information on how they support, motivate teachers to implement the evaluation system and manage the implementation process. SDTSs provided information on how they plan, supervise, coordinate, and monitor the implementation process. The eight teachers provided information on how they classify areas that needed development. The study has highlighted how teacher evaluation, IQMS should be implemented and the methods that may be used to measure teacher performance. The findings revealed that schools were not implementing teacher evaluation, IQMS as stipulated in the IQMS manual (2003), and that this might result in teachers experiencing difficulties in implementing the evaluation system and obstruct the attainment of quality teaching
Thesis (Ph.D. (Curriculum Studies)) -- University of Limpopo, 2015
Keywords: Appraisal model; Teacher quality; Teachers -- Rating of